PERLINDUNGAN HUKUM TERHADAP PEREMPUAN DALAM SISTEM PERADILAN PIDANA - muammar muammar; Nurul Mahmudah (Center of Gender Studies and Child of State Islamic Institute of Metro, 2020)
This study discusses the position of women in the criminal justice system focusing on their position as victims using a normative juridical approach. The results of the study describe that the Indonesian criminal justice system uses the Due Process Model (DPM) model and overrides the Crime Control Model (CCM). Where the position of female victims in the criminal justice system is at the level relating to compensation and rehabilitation as well as the merger of the lawsuit for compensation which is regulated in Chapter XII of the Criminal Procedure Code. Factors That Affect Legal Protection of Women Victims in the Criminal Justice System namely, the lack of Human Resources in related institutions, related to legal apparatus in related agencies and inadequate Infrastructure. The conclusion of this research is that women still need more attention in the Indonesian criminal justice system, especially women victims, as well as initiatives from policy makers to accommodate women victims of crime as parties who suffer and are harmed because they have nothing to do and not in the context of the existence and legal position of victims as the party who suffers and is harmed because of a violation of criminal law and becomes part of the criminal law.